2020
DOI: 10.3390/cells9071611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Molecular Markers of Human Th17 Cells

Abstract: Th17 cells are important players in host defense against pathogens such as Staphylococcus aureus, Candida albicans, and Bacillus anthracis. Th17 cell-mediated inflammation, under certain conditions in which balance in the immune system is disrupted, is the underlying pathogenic mechanism of certain autoimmune disorders, e.g., rheumatoid arthritis, Graves’ disease, multiple sclerosis, and psoriasis. In the present study, using transcriptomic profiling, we selected genes and analyzed the expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…Next, 5 μg RNA was used to obtain cDNA using the Maxima First Strand cDNA Synthesis Kit for RT-quantitative PCR (Thermo Fisher Scientific, Waltham, MA, USA). Real-time RT-PCR was performed using SYBR Green I Master Mix on a LightCycler 480 (Roche, Basel, Switzerland) in a 384-well white plate under the following conditions: 95 °C for 5 min followed by 45 cycles of 95°C for 10 s, 60°C for 10 s, and 72°C for 20 s. Primers for TBX21 , RORγT , IL17A , and IL17F were described previously [ 19 , 20 , 21 ]. Primers for IFNG and TNF were designed using Primer3 [ 22 ] and QuantPrime [ 23 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Next, 5 μg RNA was used to obtain cDNA using the Maxima First Strand cDNA Synthesis Kit for RT-quantitative PCR (Thermo Fisher Scientific, Waltham, MA, USA). Real-time RT-PCR was performed using SYBR Green I Master Mix on a LightCycler 480 (Roche, Basel, Switzerland) in a 384-well white plate under the following conditions: 95 °C for 5 min followed by 45 cycles of 95°C for 10 s, 60°C for 10 s, and 72°C for 20 s. Primers for TBX21 , RORγT , IL17A , and IL17F were described previously [ 19 , 20 , 21 ]. Primers for IFNG and TNF were designed using Primer3 [ 22 ] and QuantPrime [ 23 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…S4b), which could suggest their interlinked participation in keeping inflammatory responses in check. Further, co-depletion of FOSL1 and FOSL2 induced a significant increase in levels of JUNB, CD70 and APOD, all of which have reported links to Th17regulation 2,6,15,45,46,72 (Fig. S3e and Fig.…”
Section: Perturbing Fos-like Proteins Triggers Important Changes In Th17 Gene-expression Programsmentioning
confidence: 87%
“…Thus, APOD may participate in other SOX9-independent signaling pathways in the synovium tissue during OA progression. A recent study identified APOD as one of the novel molecular markers of human Th17 cells [ 59 ]. Although Th17 cells were initially investigated in RA due to their potency against autoimmune diseases [ 59 ], accumulating evidence suggests they are also increased in the OA [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified APOD as one of the novel molecular markers of human Th17 cells [ 59 ]. Although Th17 cells were initially investigated in RA due to their potency against autoimmune diseases [ 59 ], accumulating evidence suggests they are also increased in the OA [ 60 ]. Additionally, the high APOD protein level in the round ligament fat depot of severely obese women is associated with an improved inflammatory profile [ 61 ].…”
Section: Discussionmentioning
confidence: 99%